Design of Wideband Two-Sided Bandpass Frequency Selective Surface for X, Ka, and Ku Band Application - V. Vanitha; S. Esther Florence; A. Alaguraj; Lakshmi Janaki Gollamudi (International Journal of Antennas and Propagation)
A novel wideband bandpass frequency-selective surface functioning at X, Ku, and Ka bands is proposed in this article. The designed FSS has a metallic square loop and a circular ring, and they are printed on both sides of the FR4 substrate. The proposed design FR4-based single-layer FSS is operating from 11.075 GHz to 22.075 GHz with a fractional bandwidth of 66.36%. The parameters of the square loop and circular ring regulate the characteristics of the passband. The optimum dimension of these parameters is obtained with parametric analysis. The proposed structure is measured and fabricated. However, the measured results strongly agree with the simulated results, which authenticate the proposed design performance.